2020
DOI: 10.3389/fphar.2020.00001
|View full text |Cite
|
Sign up to set email alerts
|

Xiaozhang Tie Improves Intestinal Motility in Rats With Cirrhotic Ascites by Regulating the Stem Cell Factor/c-kit Pathway in Interstitial Cells of Cajal

Abstract: amount of ascites and improved intestinal motility in cirrhotic rats, which may be associated with its effect on ascites and was involved in the mechanisms regulating the SCF/c-kit signaling pathway in ICCs and improving gastrointestinal hormone secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(153 citation statements)
references
References 14 publications
4
146
0
3
Order By: Relevance
“…Furthermore, the virulence mechanism and pathogenicity of SARS-CoV2 is associated with the non-structural and structural proteins via blocking host innate immune response and by mediating viral assembly and release, successively [ 29 , 32 ]. In CoV genome, NSP3 is the largest protein and it possesses several domain activities essential for CoV replication [ 31 ].…”
Section: Molecular Mechanism and Genetic Diversity Of Sars-cov2mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the virulence mechanism and pathogenicity of SARS-CoV2 is associated with the non-structural and structural proteins via blocking host innate immune response and by mediating viral assembly and release, successively [ 29 , 32 ]. In CoV genome, NSP3 is the largest protein and it possesses several domain activities essential for CoV replication [ 31 ].…”
Section: Molecular Mechanism and Genetic Diversity Of Sars-cov2mentioning
confidence: 99%
“…Recent work reported that the respiratory droplets are associated with the contact of SARS-CoV2 transmission. It also stated that transmission occurs through airborne droplets and with close contact with each other [ 38 , 40 ]. It is important to mention that asymptomatic COVID-19 patient is also in the transmission process.…”
Section: Transmission Of Sars-cov2mentioning
confidence: 99%
“…23 TDM involves measuring the patient’s blood or plasma drug levels at the specified time to guide the dosage regimen needed to maintain levels of therapeutic ranges. 24 By combining pharmaceutical, pharmacokinetics, and pharmacodynamic knowledge, TDM enables the assessment of certain drugs’ efficacy and safety. 25 In particular, TDM provides rational support for the translation of doses to patient individual characteristics and contributes to optimizing the design of a critical phase III clinical trials, where the success of this phase represents the main conditions for drug marketing approval.…”
Section: Therapeutic Drug Monitoring (Tdm) In Generalmentioning
confidence: 99%
“… 25 In particular, TDM provides rational support for the translation of doses to patient individual characteristics and contributes to optimizing the design of a critical phase III clinical trials, where the success of this phase represents the main conditions for drug marketing approval. 24 …”
Section: Therapeutic Drug Monitoring (Tdm) In Generalmentioning
confidence: 99%
See 1 more Smart Citation